DIAGRAM POTENSI OTAK PADA ANAK AUTIS: Kajian Neurolinguistik (Brain Competence in Children with Autism: The Study of Neourolinguistics) - Gusdi Sastra, Rita Novita (Salingka, 2014)
This article talks about the analysis of brain potential diagram of autistic children through neurolinguistics.The subject of the research is the autistic children at the beginning program, intermediate program, and advanced program. Those subjects can use verbal expression. Based on the analysis, it found the differences between those subjects. The value of brain potential diagram for autistic children at early program is 4, for middle program is 8, and forthe advanced is 12. So that, brain potential of children with autistic children at advanced is better than two other program. It is proved that the brain potential of children with autistic children can be improved through a good therapy program.